2019
DOI: 10.1111/apa.15003
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal clinical blood sampling led to major blood loss and was associated with bronchopulmonary dysplasia

Abstract: Aim Studies indicate that reduced foetal haemoglobin levels are related to increased neonatal morbidity rates. This study investigated the relationships between sampling‐related blood loss and adult blood transfusions administered during postnatal days 1‐14 and the development of severe neonatal morbidities in extremely preterm infants born before 28 weeks of gestation. Methods The medical files of 149 extremely preterm infants born at two university hospitals in Sweden from 2013 to 2018 were investigated. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 41 publications
1
47
3
Order By: Relevance
“…We have previously reported that weight-related blood sample volume loss and weight-related blood transfusion volume both increase with decreasing GA at birth. 5 Importantly, the relationship between changes in mean HbF and development of BPD reported here was independent of GA at birth and other potential confounders studied. The probability for development of BPD also differed for the respective HbF quartiles across the range of GA at birth.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…We have previously reported that weight-related blood sample volume loss and weight-related blood transfusion volume both increase with decreasing GA at birth. 5 Importantly, the relationship between changes in mean HbF and development of BPD reported here was independent of GA at birth and other potential confounders studied. The probability for development of BPD also differed for the respective HbF quartiles across the range of GA at birth.…”
Section: Discussionmentioning
confidence: 54%
“…The significant decrease in HbF observed during the first postnatal week reflects current blood sampling strategy and existing laboratory infrastructure for blood sample analysis in this very preterm population and corresponds well to our previously reported findings on sample-induced blood volume loss and transfused blood volume during the first 2 weeks of life. 5 The changes in HbF levels were considerable, with a mean HbF for the whole cohort on PND 1 of 83% decreasing to a mean of 53% at PND 7. The difference in mean levels of HbF between infants who did or did not develop BPD was pronounced during the first PNDs and reached a maximum at 7 days.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our study, for each additional gram of Hb upon KMCP admission, oxygen dependency would decrease by 1.8 days and for each transfusion received, 4.8 more days of oxygen would be required. In this regard, Hellstrom et al, in a retrospective cohort study with records of 149 extremely premature babies born in Sweden between 2013 and 2018, found that blood sampling produced a 58% depletion of blood volume between days 1-14, which was correlated with the number of adult blood transfusions (r=0.87); blood loss from sampling during the first 7 days of life was related to higher BPD (adjusted OR 2.4; 95% CI 1.1-5.4) 30 . Similarly, Duan et al in a prospective cohort with 243 children <32 weeks GA in China, found early anemia significantly associated with the development of BPD (adjusted OR 4.89; 95% CI 1.57 -15.26) 31 .…”
Section: Discussionmentioning
confidence: 99%